Hubungan Status Emosional dengan Derajat Dismenore pada Remaja Putri di SMKN 12 Loa Buan Samarinda - Nurun Nimah; Anik Puji Rahayu; Aries Abiyoga (Jurnal Keperawatan Wiyata, 2021)
ABSTRACTBackground: Dysmenorrhea is a painful sensation, cramping in the lower abdomen which is often accompanied by other symptoms, such as sweating, headache, nausea, diarrhea, and tremors, all of which occur before or during menstruation. Teenage girls who experience dysmenorrhea can interfere with social or physical activities because when they are in pain, sufferers tend to be silent and even don't want to interact with other people, they tend to be more emotional. Emotional embodiment part of what a woman feels, a reaction to a certain event or situation. Emotional status and dysmenorrhea in women is a conscious experience that influences bodily activities and is psychologically able to influence a woman's emotions. Objective: To identify emotional status and to analyze the relationship between emotional status and the degree of dysmenorrhea in young girls. Methods: Quantitative research, descriptive analytic research design with cross sectional research design with proportionate stratified random sampling technique, the sample of this study was 54 students of class X SMKN 12 Loa Buah Samarinda who experienced dysmenorrheaResults: Variable emotional status obtained positive emotional classification 33 (61, 1%) and negative emotions 21 (38.9%) respondents. Variable The degree of dysmenorrhea was classified as mild 35 (64.8%), moderate 12 (22.2%), severe 5 (9.3%) and unbearable 2 (3.7%). The test used Pearson Chi-square results obtained P value = 0.402, the significant level (α) is 0.05, then p> from α. This result means that Ho is accepted, there is no relationship between emotional status and the degree of dysmenorrhea in young girls at SMKN 12 loa buah samarinda. Conclusion: There is no relationship between emotional status and the degree of dysmenorrhea in adolescents at SMKN 12 Loa Buah Samarinda